RIGOROUS AND CRITICAL EXAMINATION OF MATERIALISM PHILOSOPHY - Litri Yerisa Eribka; Sepri; Yuwita Despriyantie; Silipta; Evi Mariani (International Journal of Teaching and Learning, 2023)
This research aims to present the philosophy of materialism ontologically, epistemologically and axiologically when it encounters the life and axiology of Christian education management in the church, school and family as part of the Christian religious education space. The examination of civility, intrinsic self-value and inner beauty becomes less relevant when encountering something that is reached by the senses. They are located to the extent that they become morals. These morals are then examined in materialism as part of the purpose of education, especially Christian religious education. This research is a qualitative research with data search techniques through secondary sources, namely through recent journals as part of current research. The results of the study show the relationship between the philosophy of management, education, educational management and educational management insofar as it can be reached by the five senses and approves its integration with management that does not merely speak in abstract space or transcendence.